The Effect of Professional Orientation Toward Role Conflict WithBudget Participation and Orientation of System Goal As Moderating Variables - Sabaruddinsah Sabaruddinsah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2010)
Professionals (physicians) who work in Public Hospital and hold a structural position would have dual role both as a physician and a manager. As a physician, they should orientate on their professional values. As a manager, they have to work based on efficiency and achievement of organizational goal in running any activity. This research aims to analyze the effect of professional orientation toward role conflict and the effect of budget participation and orientation of system goal as moderating variables toward the relationship between professional orientation and role conflict. This research is performed by census method. The respondents are the physicians who hold a position as a Chief of Satuan Medik Fungsional (SMF) in public hospital of class A and B in Bekasi. The data analysis of hypothesis testing uses the Simple Regression Analysis and Moderated Regression Analysis (MRA). The results indicate that professional orientation influence role conflict positively. Budget participation and orientation of system goal are moderating variables which have negative effects toward the relationship between professional orientation and role conflict.